Non-genomic regulation of intermediate conductance potassium channels by aldosterone in human colonic crypt cells. Issue 6 (1st June 2003) - Bowley, K A; Morton, M J; Hunter, M; Sandle, G I
Abstract : Background: Aldosterone has a rapid, non-genomic, inhibitory effect on macroscopic basolateral K + conductance in the human colon, reducing its capacity for Cl − secretion. The molecular identity of the K + channels constituting this aldosterone inhibitable K + conductance is unclear. Aim: To characterise the K + channel inhibited by aldosterone present in the basolateral membrane of human colonic crypt cells. Methods: Crypts were isolated from biopsies of healthy sigmoid colon obtained during colonoscopy. The effect of aldosterone on basolateral K + channels, and the possible involvement of Na + :H + exchange, were studied by patch clamp techniques. Total RNA from isolated crypts was subjected to reverse transcriptase-polymerase chain reaction (RT-PCR) using primers specific to intermediate conductance K + channels (KCNN4) previously identified in other human tissues. Results: In cell attached patches, 1 nmol/l aldosterone significantly decreased the activity of intermediate conductance (27 pS) K + channels by 31%, 53%, and 54% after 1, 5 and 10, minutes, respectively. Increasing aldosterone concentration to 10 nmol/l produced a further 56% decrease in channel activity after five minutes. Aldosterone 1–10 nmol/l had no effect on channel activity in the presence of 20 μmol/l ethylisopropylamiloride, an inhibitor of Na + :H + exchange. RT-PCR identified KCNN4 mRNA, which is likely to encode the 27 pS K + channel inhibited by aldosterone. Conclusion: Intermediate conductance K + channels (KCNN4) present in the basolateral membranes of human colonic crypt cells are a target for the non-genomic inhibitory effect of aldosterone, which involves stimulation of Na + :H + exchange, thereby reducing the capacity of the colon for Cl − secretion.